Rewriting the Talmud The Fourth Century Origins of Bavil Rosh Hashanah - Schwartz, Marcus Mordecai (Mohr Siebeck, 2019)
Den Talmud umschreiben. Die Ursprünge des Bavil Rosch haSchana im vierten Jahrhundert.
PublicationDate: 20190710
Keywords: Yerushalmi -- Antinomie -- Talmudic Redaction -- Stam Ha-Talmud -- Amoraim -- Tannaim -- Antike -- Array